Peran Orang Percaya dalam Konservasi Lingkungan: Mengaplikasikan Ajaran Matius 5:13-16 sebagai 'Garam' dan 'Cahaya' dalam Mempertahankan Bumi yang Lebih Berkelanjutan - Paliling, Gilbert; Nunung, Donny Stevianus (Sekolah Tinggi Teologi Kharisma, 2024)
The purpose of this article is to explore the roles and responsibilities of believers in maintaining environmental sustainability, particularly in the context of natural disasters in Indonesia in 2023. This research applies a combined qualitative and quantitative method, with a focus on natural disaster data analysis and biblical interpretation, especially Matthew 5:13–16. The quantitative method involves collecting and analyzing statistical data on natural disasters from various sources, such as government reports and mass media. On the other hand, the qualitative method utilizes biblical exposition and analysis to understand the role of believers in maintaining harmony with the environment. The results show that the use of combined methods provides a holistic and contextual understanding of environmental issues. The impact of natural disasters in 2023 in Indonesia was systematically analyzed, including the number of victims, damage, and related trends. Biblical analysis illustrates the role of believers as